RANCANG BANGUN APLIKASI PUSAT OLEH OLEH BERBASIS ANDROID DI SATE BANDENG HJ.MARIYAM KOTA SERANG - Widyawati Astrabuwono; Ramdani Budiman; Hasbie Robbani (LPPM Unbaja, 2022)
Toko Sate Bandeng Hj. Mariyam located at Serang currently managed by children of Hj. Mariyam. It is a well-known tourist attraction since 1970. The main dish in the shop is milkfish satay which is always high demand by customers as they still continue to use the original recipe formulated by Hj. Mariyam. The overall sales process still performed manually from taking the order directly on the spot until payment in cash. This process have drawbacks, mainly the reduction of customers due to switching to sellers who already have easier transactions such as online transactions where it can be done anywhere and anytime, as well as problems caused by the incompatibility of the amount of sales with the amount of money in reality. This can cause losses if the calculation is carried out periodically. Another problem faced is the difficulty in the reporting process because it requires a longer time to recap all transaction and still rely on paper. The proposed system design method is waterfalls method, with the modelling use Unified Modelling Language (UML). The proposed system consider mobile-based system using Android. The proposed system can make it easier for consumers to place orders anywhere and anytime and with any payment method and make it easier for owners to manage transactions.